Single molecule microscopy reveals mechanistic insight into RNA polymerase II preinitiation complex assembly and transcriptional activity - Horn, Abigail E. (Nucleic Acids Res, 2016)
Transcription by RNA polymerase II (Pol II) is a complex process that requires general transcription factors and Pol II to assemble on DNA into preinitiation complexes that can begin RNA synthesis upon binding of NTPs (nucleoside triphosphate). The pathways by which preinitiation complexes form, and how this impacts transcriptional activity are not completely clear. To address these issues, we developed a single molecule system using TIRF (total internal reflection fluorescence) microscopy and purified human transcription factors, which allows us to visualize transcriptional activity at individual template molecules. We see that stable interactions between polymerase II (Pol II) and a heteroduplex DNA template do not depend on general transcription factors; however, transcriptional activity is highly dependent upon TATA-binding protein, TFIIB and TFIIF. We also found that subsets of general transcription factors and Pol II can form stable complexes that are precursors for functional transcription complexes upon addition of the remaining factors and DNA. Ultimately we found that Pol II, TATA-binding protein, TFIIB and TFIIF can form a quaternary complex in the absence of promoter DNA, indicating that a stable network of interactions exists between these proteins independent of promoter DNA. Single molecule studies can be used to learn how different modes of preinitiation complex assembly impact transcriptional activity.